¡Haciendo travesuras con vatos locos como yo! A low-self control approach to gang violence, gang membership, and criminal offending--violent victimization among gang members - Zavala, Egbert (Kansas State University, 2010)
Criminologists have traditionally studied criminal offending and violent victimization separately. Extant studies, however, demonstrates that criminals and victims overlap to some degree, hinting that a common underlying trait explains both criminal offending and violent victimization. This study tests whether Gottfredson and Hirschi’s self-control theory explains the overlap in criminal offending and violent victimization exposure among gang members. Using cross-sectional survey data from the Evaluation of the Gang Resistance Education and Training (GREAT) Program in the United States, 1995-1999, results from the regression models show that low self-control is to some degree correlated with criminal offending and violent victimization. Gang members were more likely than non-gang members to participate in some forms of criminal activities, but they were not more likely to be victimized. When variables stemming from social learning and social bonding are included in the regression models, results show that associating with delinquent peers had the strongest effect in predicting criminal offending, contradicting Gottfredson and Hirschi’s claim that self-control is the only cause of criminal behavior. In concert with previous studies that have found a link between low self-control and violent victimization, results show that youths with low self-control were somewhat more likely than youths with higher self-control to report being victimized. The results of the study, as well as venues for future research, are discussed.
Keywords: Gangs; Self-Control; Victimization; Criminal Behavior; Sociology, Criminology and Penology (0627); Sociology, General (0626); Sociology, Theory and Methods (0344)